The Role of Location in Indigenous and Non-Indigenous Child Oral Health - Lisa M. Jamieson, PhD; Jason M. Armfield, BA (Hons); Kaye F. Roberts-Thomson, MPH (Blackwell Synergy, 2006)
To examine the role of location in Indigenous and non-Indigenous child oral health in three Australian states and territories.